How to Assess the Value of Medicines? - Simoens, Steven (Frontiers in Pharmacology, 2010)
This study aims to discuss approaches to assessing the value of medicines. Economic evaluation assesses value by means of the incremental cost-effectiveness ratio (ICER). Health is maximised by selecting medicines with increasing ICERs until the budget is exhausted. The budget size determines the value of the threshold ICER and vice versa. Alternatively, the threshold value can be inferred from pricing/reimbursement decisions, although such values vary between countries. Threshold values derived from the value-of-life literature depend on the technique used. The WHO has proposed a threshold value tied to the national GDP. As decision makers may wish to consider multiple criteria, variable threshold values and weighted ICERs have been suggested. Other approaches (i.e. replacement approach, program budgeting and marginal analysis) have focused on improving resource allocation, rather than maximising health subject to a budget constraint. Alternatively, the generalised optimisation framework and multi-criteria decision analysis make it possible to consider other criteria in addition to value.